Is the Expression of the Components of the Carotid Matrix of Rats Influenced by Estrogen, Progestin and Tibolone? - Marcelo Luis Steiner; Thérèse Rachell Theodoro; Shirley Gimenez Garcia; Ana Maria Amaral Antonio Mader; Luciano de Melo Pompei; Maria Aparecida da Silva Pinhal; César Eduardo Fernandes (Revista Brasileira de Ginecologia e Obstetrícia, 2019)
Abstract Objective To analyze the effects of estrogen alone or in combination with progestogens and tibolone (TIB) on the expression of the extracellular matrix metalloproteinases 2 and 9 (MMP-2 and MMP-9), of perlecan, and of heparanase (HPSE) of the vascular walls of the carotid arteries. Methods A total of 30 250-day-old ovariectomized Wistar rats were orally treated for 5 weeks with: a) 1 mg/kg of estradiol benzoate (EB); b) EB + 0.2 mg/kg of medroxyprogesterone acetate (MPA); c) EB + 0.2mg/kg of norethisterone acetate (NETA); d) EB + 2 mg/kg of dydrogesterone (DI); e) 1 mg/kg of TIB; f) placebo (CTR). Following treatment, the expression of mRNA for MMP-2, MMP-9, and HPSE was analyzed by realtime polymerase chain-reaction (PCR), and the expression of MMP-2, of MMP-9, of tissue inhibitor of metalloproteinase 2 (TIMP-2), and of perlecan was quantified by immunohistochemistry in the carotid arteries. Results The groups showed significant differences on mRNA HPSE expression (p = 0.048), which was higher in the EB, EB + MPA, and TIB groups. There was no statistically significant difference in mRNA MMP-2 or MMP-9 expression. The immunohistochemical expression of MMP-2, of TIMP-2, of MMP-9, of HPSE, and of perlecan showed no differences between groups. Conclusion Estradiol alone or associated with MPA and TIB treatment can increase mRNA HSPE expression of the walls of the carotid arteries in ovariectomized rats.